2011
DOI: 10.2310/7290.2010.00053
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanoparticles: Detection of Long-Term Transgene Activity in Brain using Bioluminescence Imaging

Abstract: In this study, we used bioluminescence imaging (BLI) to track long-term transgene activity following the transfection of brain cells using a nonviral gene therapy technique. Formulations of deoxyribonucleic acid (DNA) combined with 30-mer lysine polymers (substituted with 10 kDa polyethylene glycol) form nanoparticles that transfect brain cells in vivo and produce transgene activity. Here we show that a single intracerebral injection of these DNA nanoparticles (DNPs) into the rat cortex, striatum, or substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
5
28
0
Order By: Relevance
“…Non-viral vectors, such as Copernicus' PEG-CK30 compacted plasmid DNA NPs, are certainly of high priority as they have been shown to be effective by this route in a PD model. Several key advantages of PEG-CK30 NPs are their ability to enter the cell's nucleus, to transfect cells in the brain, and to avoid inducing immunogenic and inflammatory responses when given via the nose [148,[150][151][152]154]. These PEG-CK30 NPs might still be optimized to improve nasal mucous penetration, increase delivery to the brain, enhance tissue penetration, or to target different cell types for transfection.…”
Section: Which Vectors Which Genes?mentioning
confidence: 96%
See 1 more Smart Citation
“…Non-viral vectors, such as Copernicus' PEG-CK30 compacted plasmid DNA NPs, are certainly of high priority as they have been shown to be effective by this route in a PD model. Several key advantages of PEG-CK30 NPs are their ability to enter the cell's nucleus, to transfect cells in the brain, and to avoid inducing immunogenic and inflammatory responses when given via the nose [148,[150][151][152]154]. These PEG-CK30 NPs might still be optimized to improve nasal mucous penetration, increase delivery to the brain, enhance tissue penetration, or to target different cell types for transfection.…”
Section: Which Vectors Which Genes?mentioning
confidence: 96%
“…These NPs compact a single molecule of expression plasmid, have a minimum diameter of 10 nm, and can be formulated in a rod-like shape [148][149][150]. They are non-immunogenic, non-inflammatory, small enough to enter the cell's nucleus via the nuclear membrane pore and able to transfect postmitotic cells in the brain, lung, and retina [148,[150][151][152][153][154]. We first Intranasal gene delivery for treating PD Expert Opin.…”
Section: Non-viral Vectorsmentioning
confidence: 98%
“…Although both constructs generated similar levels of GDNF one week after intranasal administration (Figure 25), GDNF expression may have been more sustained over the one month after dosing with the NPs than with the naked plasmid, thereby generating more neuroprotection during the course of lesion development. In support of this conclusion, DNA NPs were previously shown to yield longer--lasting expression than the naked plasmid after injection into the rat brain 239,242 . While an acute, neurotoxin--induced lesion of SN dopamine neurons is not mechanistically or temporally comparable to the gradual, progressive course of human PD, these results confirm the tremendous potential of intranasal pGDNF_1b, and the nanoparticle vector, as means of protecting and rescuing dopamine neurons from a severe neurotoxic insult.…”
Section: Image Pre--gd Image Post--gd Subtraction In Matlabsupporting
confidence: 58%
“…Copernicus Therapeutics Inc. has engineered several DNA plasmids controlled by the polyubiquitin C promoter that are the focus of our work. These include a plasmid for human GDNF (pGDNF_1b DNA NPs is capable of transfecting cells in both rat and mouse striatum with high transfection efficiency, yielding protein expression lasting longer than a year 242 . Copernicus has also generated a pGDNF_1b plasmid that includes the coding sequence for enhanced green fluorescent protein (eGFP).…”
Section: Development Of An Intranasal Gdnf Gene Therapy: Preliminary mentioning
confidence: 99%
“…1 These NPs have also been successfully used in the lung and brain [10][11][12][13][14] and result in no toxic effects in the eye 5,6,15 even after repeated subretinal injection. 5 Perhaps most excitingly, these NPs have a large capacity; we have shown that they can successfully incorporate and deliver DNA of up to 14 kbp in photoreceptors (largest size tested) 9 without significant decrease in transduction efficiency, and others have demonstrated effective transfection in the lung with plasmids of up to 20 kbp (largest size tested).…”
Section: Introductionmentioning
confidence: 99%